Adaptasi Komunikasi Penutur Dialek Ngapak Diluar Lingkungan Budaya Lokalnya - Pingki Setiyo Anggraeni; wiwid Noor Rakhmat (Interaksi Online, 2020)
This research is about of the ngapak dialect in Semarang who no longer use Banyumasan as their native language. They feel ashamed and insecure when using Banyumasan Language because it is often considered a low class language and used as a joke by other people. So this study aims to determine the adaptation of communication by speakers of the local dialect outside the local cultural environment through a phenomenological approach. This study uses the foundation of Communication Accommodation Theory, using data collection techniques in the form of in-depth interviews involving four speakers of the ngapak dialect in the city of Semarang. The findings of this study indicate that interaction carried out by individuals who speak dialect with individuals from other cultures raises several obstacles, including the differences in the language of each culture such as vocabulary, dialect, delivery methods, and expressions. Then the lack of knowledge about the information values that are owned by each culture. Furthermore, it is followed by various perceptions about individuals from other cultures and the emergence of anxiety, fear and discomfort when communicating with individuals from other cultures. Constraints that arise during the process of communication adaptation take place make speakers of the dialect make accommodation efforts to avoid and overcome existing obstacles. To achieve accommodation there is a way that is done by speakers of the dialect, namely by convergence, such as by slowing down the speed of speech and equating their speech dialect into Semarang accent. In addition, speakers of the Ngapak dialect also try to open themselves by learning the local language and trying to accept various cultures that are around them. Based on this research, it can be concluded that speakers of the native Ngapak dialect adapting communication with individuals from other cultures and make accommodations in the form of convergence that is by adjusting the local language, and they open themselves to the culture around them.